The delivery man - McGinniss, Joe, Jr., 1970- (New York : Black Cat, 2008)
The lucrative yet dangerous world of a teenage call-girl service lures Chase and his childhood friend, Michele, in Las Vegas
Keywords: Teeage prostitution -- Los Vegas; Man - women relationship -- Fiction